Defenders of the Faith: Ottawa’s Anglicans and the First World War - McIntyre, Heather (Ontario History, 2024)
This article uses day-to-records such as vestry notes, financial records, and local newsletters, to establish that during the First World War the Anglican Diocese of Ottawa urged regular intercessory prayer for an Allied victory, encouraged pro-war rhetoric from its pulpits, and used its priests to encourage conscription. They sought to foster an identity in which Canadian patriotism and loyalty to Empire were synonymous, and in which the Empire was a force for God’s will in a war that could destroy Western civilization. Despite a slow start, lay Anglicans remained committed to the war effort, especially through large-scale volunteer efforts that contributed to local soldiers. As manpower needs became greater and conscription became a pressing issue, they increased their efforts in war work and recruitment drives.